Man and Women : The Question of Equal Opportunity. Final Report - Solmon, Lewis C.; Higher Education Research Inst., Inc., Los Angeles, CA.; California Univ., Los Angeles ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
This study of differential opportunities for men and women graduate students was undertaken for several reasons: (1) to help reach a consensus on a proper and operational definition of sex discrimination in graduate schools; (2) to turn the debate over sex discrimination toward efforts to document quantitatively the allegations previously substantiated by anecdotes; (3) to see whether the affirmative action legislation regarding students, which has been imposed on graduate institutions and caused great havoc in their operation, is required or justified, that is, whether it is the fault of institutions or of earlier conditioning of both sexes by society. The document begins with a review of earlier discussions of sex discrimination in graduate schools. This review is followed by attempts to document and explain differences by sex in the admissions process, time spent in graduate study, geographic and interinstitutional mobility, and financial aid practices. It is in these areas that the most explicit charges of differential treatment of the sexes have been made; these are also areas where new data can be brought to bear on the issue. Appendixes cover a survey of graduate school catalogues, doctoral-granting institutions that provide useable data on acceptable rates, and a survey of institutional studies. (Author/KE)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Educational level discussed: Higher Education.
Microfiche.
Keywords: Admission Criteria; Affirmative Action; Doctoral Programs; Equal Protection; Federal Legislation; Financial Support; Geographic Location; Graduate Students; Graduate Study; Higher Education; School Catalogs; Sex Discrimination; Student Mobility; Reports, Research